Regulating the Use of Artificial Intelligence(AI): Achievements and Challenges - Hamamoto, Mayumi (University of Saint Joseph, 2024)
This dissertation is research regarding the achievements and challenges in artificial intelligence (A) regulation at a domestic level and international level. This study is important because there are more legal issues regarding the application of AI, and AI has grown to be part of the public’s daily lives. A mixed method has been adopted in this research: doctrinal legal research and a comparative legal research method. AI was invented in the 1950s and in the 2000s, has been more accessible to the public. The first AI regulation, the EU AI ACT, has recently been enforced, an AI regulation that has been around for nearly seven decades after its invention. It is high time that regulators in different states invest more effort in AI regulations
Keywords: AI; Artificial Intelligence; System Learning; Thesis and Dissertations Master of Lusophone and International Public Law(MLIPL); University of Saint Joseph

Study of the Cross-Border Family Mediation Mechanisms and Practices in the Greater Bay Area (China, Hong Kong SAR, and Macau SAR”) - Wong, Hang Si (University of Saint Joseph, 2024)
The dissertation is about the study on the usage of mediation as the dispute mechanism on the cross-border family dispute issue in the Guangdong -Hong Kong- Macau Greater Bay Area through a comparative law aspects. Under the background of the Country’s Policy in integrating the citizens of the two SARs into China. The citizens of different provinces in PRC and the two SARs have frequent contact such as in business, in personal affairs and so on, the more the contact the more the possibility disputes will arise. With three different jurisdictions and the backlogs from the Courts, to find out the possibility of using another dispute resolution is essential. The study found out the perspectives of the disputed / litigated parties, courts and legal practitioners in usage of mediation, the nature of mediation in use in GBA and the strengths and limitations on the usage of mediation. This research used a mixed methods including doctrinal legal research, comparative legal research method and empirical legal research method. It result from the finding that though there is no specialized legislation in usage of mediation in Macau SAR, there is practice in usage of family mediation. Besides that the judicial mediation in PRC is not the mediation we defined in the literature review, thus it is the conciliation. Whether the recent development in Hong Kong SAR on the procedures M-FDR and M-CDR are in conflict with the facilitative mediation which has all along been practiced in Hong Kong SAR. In conclusion, the perspectives in usage of mediation in PRC and Hong Kong SAR are higher than Macau SAR and the nature of mediation in usage are different in the three jurisdictions. Lastly, in the dissertation provided some reflections on the development of family mediation mechanism in Macau SAR and how to merge the different natures of mediation in GBA
Keywords: ADR; Alternative Dispute Resolution; GBA; Greater Bay Area; Mediation; Mediation Mechanism; Thesis and Dissertations Master of Lusophone and International Public Law(MLIPL); University of Saint Joseph

CONSUMER PROTECTION POLICY IN MACAO'S FINANCIAL SERVICES SECTOR: ANALYSIS OF THE STRENGTHS AND WEAKNESSES IN COMPARISON TO GLOBAL PRACTICES - Kuan, Ho Tong (University of Saint Joseph, 2024)
This research is to assess the current status quo, strengths, and weaknesses of financial consumer protection mechanisms in Macao. According to the World Bank, financial consumer protection can bring positive impact on the development of financial sector, broadening financial inclusion and fostering economic growth. In 2022, under the backdrop of COVID-19 and downturn in economy, Macao Government announced its ambition to recover and diversify the economy of Macao by leveraging “1+4” Diversified Development Strategy, in which developing modern finance is one of the main priorities. The new Financial System Act took into effect on 1st November 2023 and this Act will enable non-financial institutions to apply for temporary licenses on fin-tech innovations within a controllable risk area. In the local context, does Macao have a strong financial consumer protection mechanism in place to goal for developing modern finance and face challenges brought by fin-tech? In this research, a mixed method consisting of doctrinal legal research method and comparative legal research method is adopted. 10 jurisdictions (Ireland, Singapore, Australia, United Kingdom, Malaysia, Hong Kong, China, European Union, Canada, and United States) were selected in comparison of rights for financial consumer protection based on the G20/OECD High-Level Principles on Financial Consumer Protection and the results of which were then compared to the rights for financial consumer protection in Macao. The findings of this study show that the main strength of financial consumer protection mechanisms in Macao lies on the supervision of the Monetary Authority of Macao (AMCM) on the banking sector and insurance sector, other financial institutions according to international principles; however, the in-depthness of work done by Macao in financial consumer protection is not as much as those done by other jurisdictions: in Macao, there is no policyholder protection scheme in the event of failure of insurance companies; no mystery shopping and consumer survey done by oversight bodies; narrow range of definition of vulnerable consumers; no financial literacy survey; no in-depth competition law; no in-depth guidelines to monitor advertising materials for financial products; no database for consumers to search for unregulated firms and scammers; no in-depth financial educational materials about the rights of financial consumers. It is recommended that Macao Government can learn from United Kingdom, Canada and European Union to adopt behavioural insights in developing financial consumer protection policy to protect financial consumers from being exploited by the financial service providers based on the consumers’ behavioural biases. Some literature suggested that consumers are vulnerable in digital landscape. Therefore, it is strongly recommended that Macao Government shall take proactive actions to strengthen the current financial consumer protection mechanism by adhering to the G20/OECD High-Level Principles on Financial Consumer Protection, in order to develop modern finance and protect consumers from the risks posed by fin-tech
Keywords: Macao; Thesis and Dissertations Master of Lusophone and International Public Law(MLIPL); University of Saint Joseph; financial consumer protection; financial education; financial inclusion; financial literacy

The international law against tax avoidance: “status quo” and perspectives for development of the regime - Wong, Chang Man (University of Saint Joseph, 2024)
This dissertation examines the critical need to continuously update the international tax law against tax avoidance: “status quo” and perspectives for development of the current regime. Employing a doctrinal methodological approach, the research first seeks to uncover the most common forms of international tax avoidance through an extensive literature review. This crucial step provides invaluable insights into the diverse strategies and mechanisms utilized by individuals and businesses to circumvent taxation on a global scale. The dissertation then proceeds to examine how current international tax law addresses the identified forms of tax avoidance. This implies a multi-faceted analysis, including an identification of the relevant international norms and treaties, and an exploration of the main sources of international tax law and their practical application. Recognizing the dynamic nature of the global tax landscape, the dissertation also provides perspectives for the future development of international tax law to better address the challenge of tax avoidance. By thoroughly examining the strengths and limitations of the current international tax law regime, the dissertation offers recommendations for potential improvements to the application of international tax avoidance conventions. The findings of this comprehensive study contribute to the broader understanding of international tax avoidance and its regulation within the framework of international law. The research questions and objectives serve as a guiding framework, enabling a thorough analysis that can inform practitioners, and scholars engaged in the ongoing discourse surrounding global taxation and its implications for economic fairness and transparency
Keywords: Global taxation; International norms and treaties for tax; International tax avoidance; International tax law against tax avoidance; Limitation and development of current international tax law regime; Status quo; Thesis and Dissertations Master of Lusophone and International Public Law(MLIPL); University of Saint Joseph

Comparative study of the implementation of the National Security Law in the SARs: A Case study of Hong Kong SAR and Macao SAR - Wu, Ka Seng (University of Saint Joseph, 2024)
The aim of this study is comparing the jurisdiction of the National Security Law in Hong Kong SAR and Macau SAR, also reviewing the practical implementation of the law in the two SARs, analyzing the Chinese government's participation in the governance of national security in two SARs, and exploring the future sustainability of National Security Law in two SARs
Keywords: Hong Kong; Macao; National Security; National Security Law; Thesis and Dissertations Master of Lusophone and International Public Law(MLIPL); University of Saint Joseph

TURNING THE SDGS INTO LEGAL COMMITMENTS: Catarine Isabel Pereira Batista - Batista, Catarine Isabel Pereira (University of Saint Joseph, 2024)
This dissertation examines the current implementation of specific Sustainable Development Goals (SDGs) within the Macau legal system, despite the non-mandatory nature of these goals and how they were implemented. The SDGs, established by the United Nations, provide a comprehensive framework for addressing global social, economic, and environmental challenges. While Macau is not obliged to adopt the SDGs, this study aims to explore the extent to which the principles and objectives of specific SDGs have been integrated into the legal system of Macau. Through an analysis of relevant laws, and policies, this research seeks to identify alignment and visible gaps between the SDGs and the Macau legal framework. The findings of this study may contribute to a deeper understanding of the voluntary implementation of the SDGs in Macau and provide insights for other jurisdictions facing similar circumstances
Keywords: Hard Law; International Law; Legal system; Macau SAR; Soft Law; Sustainable development goals; Thesis and Dissertations Master of Lusophone and International Public Law(MLIPL); University of Saint Joseph